2016
DOI: 10.1002/oby.21616
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of a nationally available weight control program tailored for adults with type 2 diabetes

Abstract: Objective: Modest weight loss from clinical interventions improves glycemic control in type 2 diabetes (T2DM). Data are sparse on the effects of weight loss via commercial weight loss programs. This study examined the effects on glycemic control and weight loss of the standard Weight Watchers program, combined with telephone and email consultations with a certified diabetes educator (WW), compared with standard diabetes nutrition counseling and education (standard care, SC). Methods: In a 12-month randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…This digital program exceeded the CDC session requirement in all three cohorts. Depending on the type of cohort analyzed, 23% to 36% of the participants lost 5% or more of their body weight, which is similar to the range of 18% to 34% reported by O'Neil et al who examined the impact of adding telephonic and email counseling from a diabetes educator alongside an in-person commercial weight-loss program (19). The participants in Real Appeal also had similar results reported in a digital DPRP program (21), with the major difference being the size of the study samples being compared.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This digital program exceeded the CDC session requirement in all three cohorts. Depending on the type of cohort analyzed, 23% to 36% of the participants lost 5% or more of their body weight, which is similar to the range of 18% to 34% reported by O'Neil et al who examined the impact of adding telephonic and email counseling from a diabetes educator alongside an in-person commercial weight-loss program (19). The participants in Real Appeal also had similar results reported in a digital DPRP program (21), with the major difference being the size of the study samples being compared.…”
Section: Discussionsupporting
confidence: 69%
“…The ability of Real Appeal to engage with 52,461 weight-loss participants during a 12-month period was remarkable. These participants had outcomes similar to those reported by other commercial weightloss programs (19,20) and digital DPP programs (21). When assessing the effectiveness of a DPP program, the CDC examines the average number of sessions attended by program participants, with an average of nine sessions required to achieve full CDC DPRP recognition (10).…”
Section: Discussionmentioning
confidence: 89%
“…Nine trials comprised education alone, the remaining 40 were multicomponent. Participant contacts were quantified in 46 trials, ranging from one contact over 6 months [S18] to 107 contacts over 12 months [38]. Thirty trials described duration of each contact, which ranged from 5 min [41] to 150 min [35,37, S12].…”
Section: Intervention Descriptionmentioning
confidence: 99%
“…All five trials pre-selecting participants showed significant effects on weight/BMI [31,34,36,39,S18]. All five trials providing extra contacts with intervention staff, if required, saw significant effects on weight [38,40,45,S14,S19]. Eight of the nine trials providing personalized feedback showed significant effects on weight/BMI [28,32,39,42,45,S4,S15, S19].…”
Section: Weight and Bmimentioning
confidence: 99%
“…The current study had three aims: (1) to determine the extent to which adults engaged in weight loss reported WBI; (2) to identify correlates of WBI, including demographic characteristics and specific types of weightstigmatizing experiences; and (3) to compare these correlates between WBI measures (WBIS-M versus WSSQ). These aims were evaluated in a large sample of adults enrolled in WW (the new Weight Watchers), an empirically validated behavioural weight management programme that encourages healthy habits related to food, activity and mindset (19)(20)(21)(22). Given that millions of Americans participate in weight management programmes each year (23), these treatment-seeking adults may represent a more generalizable sample than those from prior smaller, more tightly controlled treatment efficacy studies in clinical settings.…”
Section: Introductionmentioning
confidence: 99%